Планирање во глобалните претпријатија - Ристовска, Наташа (Економски факултет, УКИМ, Скопје, 2012)
The fast rate of globalization renders the traditional ways of doing business irrelevant and leads to the emergence and increasing importance of global business planning and global mindset. The aim of this doctoral dissertation is to provide an understanding of the enterprise planning function and activity in modern conditions of operation. The survey focuses on the planning process in global enterprises. Explanation of the steps and phases in the global planning process, and discussion about the importance of formulating appropriate goals and strategies for entering the global market, is included. This thesis provides an understanding of key functional aspects of global business planning. It also talks about the instruments for planning and related software programs supporting the planning process in global enterprises. The preparation of global business plans is closely analyzed. Finally, the paper examines the characteristics of the system of global strategic planning, necessary for the global enterprises to deal with rapidly changing global environment, to meet new competition, and to achieve strategic goals. Finally, the theoretical discussion of the challenges for effective planning in global enterprises is supported by the results of the conducted empirical research in several global enterprises in the Republic of Macedonia, determining the business planning practices and the role, the importance and the necessity of planning for successful realization of their objectives.
Planning in global enterprises
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Бобек Шуклев.
Keywords: globalization, global market, global strategy, global enterprise, global business planning, global strategic planning